The Power of Knowledge: How CEO Education Shapes CSR Transparency in Indonesian Banks - Satrio Nararya; Syahriar Abdullah; Rahmatya Widyaswati (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study examines the impact of CEO education on Corporate Social Responsibility disclosure in Indonesian banks, with a focus on the role of CEO characteristics in shaping corporate social practices. Using data from banks listed on the Indonesia Stock Exchange, the study explores the relationship between CEO education level, CEO background in finance, and CSR disclosure, applying the Upper Echelons Theory (UET) to explain how CEO characteristics influence corporate decision-making. The findings reveal a significant positive relationship between CEO education level and CSR disclosure, suggesting that CEOs with higher education are more likely to lead firms that disclose comprehensive CSR information. Conversely, CEOs with a finance background were found to have a negative impact on CSR disclosure, indicating a preference for financial performance over social responsibility. Additionally, company size was found to significantly influence CSR disclosure, with larger companies more likely to engage in CSR reporting. The study contributes to the growing body of literature on CSR disclosure by highlighting the role of CEO education in shaping corporate transparency, particularly in the banking sector. The findings also underscore the need for a balanced perspective in leadership, where a broader commitment to social responsibility and sustainability complements financial expertise.